(untitled) (Research, Society and Development, 2024)
This study aimed to evaluate the impact of altitude on the anatomical characteristics of Ocotea indecora wood under various relief conditions in Cunha, São Paulo. Non-destructive stem samples of Ocotea indecora were collected at three altitudes within the Cunha Nucleus of the Serra do Mar State Park (1300, 1200, and 1000 m). Five non-destructive samples were taken at each altitude around the diameter at breast height (DBH) of selected trees. Trees above 1250 m were situated in plateau areas, while the remaining sampled trees were situated in escarpment areas with slopes ranging from 30 to 90%. The geolocation of sampled trees was performed using global positioning system equipment. The samples were processed following standard wood anatomy techniques. Significant differences were observed, but only in the fiber diameter of samples collected between 1000 m and 1300 m. At 1300m, fiber diameter showed the highest values, while the lowest fiber diameter was found in trees sampled at 1000 m. According to cluster dendrogram analysis, considering all analyzed variables, altitudes of 1200 m and 1300 m were grouped together, differing from the altitude of 1000m, which formed a separate cluster. Generally, anatomical elements correlate differently among themselves depending on the altitude gradient.